Does The Sales Stability Effect the Relationship Between Growth Opportunity, Asset Structure and Capital Structure - Mardhyana Agustina (Universitas Pamulang, 2024)
The research aims to determine the effect of Growth Opportunity and Asset Structure on Capital Structure with Sales Stability as a moderation variable on companies listed on the Indonesian Stock Exchange from 2018-2022. The population was 375 companies. Based on the purposive sampling method, samples from 75 companies were obtained. The method of analysis used is the method of double linear regression analysis. This research shows that (1) Growth Opportunity has a negative and significant impact on the Capital Structure because the company has an increased total of assets. Increased total assets enable the company to carry out operational activities using acquired assets and reduce debt. (2) Asset structure positively and significantly influences capital structure since a company with increased assets can still guarantee its fixed assets to the creditor. This condition makes the company more confident in guaranteeing the Fixed Assets. (3) Selling Stability can moderate the influence of the growth opportunity on capital structures because a company with Stability of sales will be confident to use its debt as a source of financing to enhance growth opportunities; (4) Selling Stability is unable to Moderate the impact of the asset structure on the modal Structure as the company is more likely to view the effect of sales stability on net earnings, otherwise with asset composition management or capital structure policy.